Ảnh hưởng của các chất đóng rắn đến tính chất cơ lý của màng phủ polyme trên cơ sở nhựa epoxy epikote 828 - Bích Thủy, Nguyễn Thị; Minh Ngọc, Phan Thị; Diệu, Trần Vĩnh; Trung, Đặng Hữu; Yến Oanh, Đoàn Thị (Vietnam Journal of Chemistry, 2014)
In epoxy compositions, hardener plays very important role. Correct choice of hardener will solve both questions-improving toughness and molecular network of epoxy materials. Cyanethyldiethylenetriamine (CEDETA)-adduct of diethylenetriamine and acrylonitrile has been used as hardener. Having low viscosity, CEDETA can used in composites, adhesives and coatings. Commercial hardener Versamid 115 is mainly used in epoxy coatings. In this work, when using CEDETA hardener, curing level reach maximal value 85 % with coefficient k = 1.2. For Versamid 115, curing level reach maximal value 99.5 % with ratio Epikote 828/Versamid 115 = 100/100 wt%. Curing energy activation of CEDETA and Versamid 115 are 12.62 kcal/mol and 3.73 kcal/mol respectively. It is indicate that curing reaction of Versamid 115 is more moderate process. Dispersion of CTBN in epoxy resin Epikote 828 was treated with an ultrasonic vibrator for 15 minutes. Both of hardener CEDETA and Versamid 115 possess good physico-mechanical properties of polymer epoxy coating films. Keywords: Hardener, epoxy resin, curing